Effects of Teaching Practices on Life Satisfaction and Test Scores: Evidence from the Program for International Student Assessment (PISA) - Kelsey J. O'Connor; Stefano Bartolini (Institute of Labor Economics (IZA), 2024)
Schools are ripe for policy intervention. We demonstrate that a greater prevalence of group discussion used in schools positively affects students' life satisfaction and noncognitive skills but has no impact on test scores, based on a sample from the 2015 PISA which includes more than 35 thousand students from approximately 1500 schools in 14 countries. We perform regressions of student life satisfaction on school-level group discussion and lecturing, including a battery of controls and random intercepts by school. For robustness we use instrumental variables and methods to account for school-selection. The impact of group discussion is meaningful – a one-standard-deviation increase leads to an increase in life satisfaction that is about one-half of the negative-association with grade repetition. In contrast, lecturing does not have any effects. We are the first to show group discussion improves student life satisfaction and noncognitive skills, and thereby likely positively affects later-life outcomes.
Keywords: I21; I31; J24; 330; participatory teaching; test scores; noncognitive skills; teaching practices; subjective well-being; horizontal teaching